An approach to determine the easy axis of magnetic film by anisotropic magnetoresistance measurements. (12th March 2020) - Du, Wei; Tang, Xiaoli; Liu, Mengli; Su, Hua; Han, Genliang; Lu, Qihai
Abstract: A series of Ta/NiCo/Ta films was grown through DC-sputtering. During deposition, a constant magnetic field was applied along the substrate in different directions to induce different orientations of the easy axis. Three different magnitudes of external fields were applied in the angle-dependent anisotropic magnetoresistance (AMR) measurements of the samples. Through an effective analysis, the angle-direction extracted via the intersection of three angle-dependent AMR curves was confirmed as the easy axis. Compared to the normal methods applied to achieve the easy axis, the results are convincing. This new method provides an effective, convenient and low cost way of studying magnetic materials and devices.